Reactivity of CO and C2H4 on Bimetallic PtxAg1‐x/Pt(111) Surface Alloys Investigated by High‐Resolution X‐ray Photoelectron Spectroscopy. Issue 12 (19th April 2018) - Bauer, Udo; Späth, Florian; Düll, Fabian; Bachmann, Phillip; Steinhauer, Johann; Steinrück, Hans‐Peter; Papp, Christian
Abstract: We have investigated the adsorption and thermal reactivity of CO and C2 H4 on well‐defined bimetallic Ptx Ag1‐x /Pt(111) surface alloys (with x=0.67, 0.50, 0.38 and 0.32) using in situ synchrotron‐based high‐resolution X‐ray photoelectron spectroscopy. During low‐temperature (140 K) adsorption of CO, we find population of the energetically more stable Pt on‐top site followed by the Pt bridge site, as known from clean Pt(111); CO does not adsorb on Ag facets under the applied conditions. The total CO coverage linearly decreases with Ag surface content. Upon heating, COon‐top and CObridge desorb at higher temperatures than on bare Pt(111), for example, by ∼65 K for COon‐top for an Ag content of 33 %. This shift is due to the well‐known electronic ligand‐effect of Ag atoms surrounding Pt atoms/clusters. For C2 H4 adsorption on the AgPt alloys at low temperature (120 K), we find two species in the C1s XP spectrum, each displaying a vibrational fine structure; this contrasts the situation on clean Pt(111), where only one species is found. Upon heating, ethylene reacts with ethylidyne being the dominant intermediate; in contrast to clean Pt(111), on the alloy surfaces the reaction to CCH3 occurs at much lower temperatures, e. g. by ∼60 K for the alloy with 68 % Ag, and no ethylene desorption is found. Abstract : Alloying for increased reactivity : Alloying a Pt(111) surface with Ag atoms in the first layer can alter the catalytic activity of the system. Independently of the Ag coverage, CO adsorbs on on‐top and bridge sites and bounds more strongly with increasing Ag content. Ethylene exhibits an identical reaction pathway compared to Pt(111), but the reaction temperatures are reduced.